2019
DOI: 10.1016/j.immuni.2018.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoid Dendritic Cells: Development, Regulation, and Function

Abstract: Plasmacytoid dendritic cells (pDCs) are a unique sentinel cell type that can detect pathogen-derived nucleic acids and respond with rapid and massive production of type I interferon. This review summarizes our current understanding of pDC biology, including transcriptional regulation, heterogeneity, role in antiviral immune responses, and involvement in immune pathology, particularly in autoimmune diseases, immunodeficiency, and cancer. We also highlight the remaining gaps in our knowledge and important questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
485
1
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 470 publications
(550 citation statements)
references
References 185 publications
13
485
1
6
Order By: Relevance
“…These lymphoid characteristics may result from their shared expression of Bcl11a, which controls RAG-1 expression (Lee et al, 2017). Alternatively, they may be a consequence of an ectopic lymphoid program activated by TCF4, as previously suggested (Reizis, 2019). We found that tDCs, especially CD11c high tDCs, simultaneously express PTCRA-EGFP and Zbtb46, a TF generally associated with cDCs.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…These lymphoid characteristics may result from their shared expression of Bcl11a, which controls RAG-1 expression (Lee et al, 2017). Alternatively, they may be a consequence of an ectopic lymphoid program activated by TCF4, as previously suggested (Reizis, 2019). We found that tDCs, especially CD11c high tDCs, simultaneously express PTCRA-EGFP and Zbtb46, a TF generally associated with cDCs.…”
Section: Discussionsupporting
confidence: 77%
“…The exact developmental origin of tDCs also requires further study. It is possible that tDCs are generated as a byproduct of pDC development, as suggested for noncanonical DCs (Reizis, 2019). Alternatively, tDCs may arise directly from pDCs.…”
Section: Discussionmentioning
confidence: 99%
“…These cells then stop producing IFN-I (Duramad et al, 2003;Colonna et al, 2004;Ito et al, 2006) and can then activate T cells, becoming key players in the adaptive response. The role of pDCs in linking innate and adaptive immunity to control viral infections has been well documented and reviewed (Colonna et al, 2004;Reizis, 2019). Because of their ability to contribute to both innate and adaptive responses, pDCs have been a cell type of great interest (Reizis et al, 2011), and numerous trials are underway to activate these cells in various disease indications (Reizis, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This is a timely question as many drugs targeting either the IFN pathway or pDCs directly are currently being evaluated in large clinical trials with various amounts of success (Table 1). The discovery and initial characterization of pDCs have been discussed in multiple review articles (Liu, 2005;Guiducci et al, 2009;Tang et al, 2010;Reizis et al, 2011;Vermi et al, 2011;Swiecki and Colonna, 2015;Reizis, 2019), so we will focus on discussing the role that they may play in promoting autoimmunity and then describe novel findings linking pDC activation and IFN-I production during chronic infectious diseases. We will also summarize the various approaches currently in clinical development that target pDCs or the IFN-I pathway, and discuss how much extrapolation can be made from recent clinical trials targeting IFN-I.…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, we have found that SMAD3 deficiency in vivo resulted in substantial loss of pDCs and pre-pDCs, indicating the indispensable role of SMAD3 for pDC differentiation at the developmental stage of pre-pDCs. We have found that low-dose TGF-β in vitro that represents in vivo steady-state physiological function (Zi et al, 2012) transactivates SMAD3 in BMDCs, which then induces pDC-related genes: Spib, Tcf4 and Ikaros (Allman et al, 2006;Cisse et al, 2008;Ghosh et al, 2010;Nagasawa et al, 2008, Reizis et al, 2019. Significantly more profound decrease of pDCs in SMAD3 deficient mice compared with the mice deficient in E2-2 (Ghosh et al, 2010;Grajkowska et al, 2017) also supports our finding that SMAD3 is the upstream inducer of these pDC-related genes.…”
Section: Discussionmentioning
confidence: 99%